PENGARUH PEMBERIAN PISANG RAJA TERHADAP INDEKS KELELAHAN OTOT FASE ANAEROB ANGGOTA RESIMEN MAHASISWA 804 UNIVERSITAS NEGERI SURABAYA - Wibawa, Junian Cahyanto; Noordia, Anna (Jurnal Kesehatan Olahraga, 2019)
Background: The anaerobic phase of muscle fatigue occurs because of the accumulation of lactic acid which causes pain and inhibits muscle contraction. ?Pisang Raja? contains of high carbohydrates and potassium which will increase blood glucose levels, thus potentially preventing muscle fatigue. The aim of the study was to examines  the effect of the Pisang Raja in  index of muscle fatigue of the 804 Student Regiment Surabaya State University??s anaerobic phase. Method: This study used a quasi-experimental design , which only use post test with control group design. The subjectsof this research  were 12 members of the 804 Student Regiment, State University of Surabaya. At the pre-test, 220 ml of mineral water were received, and post-test received 220 ml mineral water and 250 Pisang Raja. Anaerobic phase muscle fatigue was measured using the RAST test (Running-based Anaerobic Sprint Test) by calculating the value of AF (Anaerobic Fatigue). The data were analyzed by using the Independent Sample Test. Results: Average pre-test AF index (4.85), while post-test (3.57) so that AF decreased between pre-test and post-test. Conclusion: There is the effect of the Pisang Raja in reducing the anaerobic phase of muscle fatigue index in the 804 Student Regiment of State University of Surabaya. Keywords: Pisang Raja , anaerobic phase muscle fatigue, RAST